2015
DOI: 10.1017/s0967199415000349
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive assessment of porcine oocyte quality by supravital staining of cumulus–oocyte complexes with lissamine green B

Abstract: SummaryWe evaluated the usefulness of lissamine green B (LB) staining of cumulus-oocyte complexes (COC) as a non-invasive method of predicting maturational and developmental competence of slaughterhousederived porcine oocytes cultured in vitro. Cumulus cells of freshly aspirated COCs were evaluated either morphologically on the basis of thickness of cumulus cell layers, or stained with LB, which penetrates only non-viable cells. The extent of cumulus cell staining was taken as an inverse indicator of membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…In Dutta et al (2016) successful maturation rate was reached 79.9% in A grade group, which is very similar to our control group (74.03%). With porcine A grade oocytes (high quality oocytes after LB staining), the successful maturation rate reached 84.70%, which is almost identical to our LB-oocytes (82.24%).…”
Section: Proteomic Evaluation Of Lb-and Lb+ Oocytessupporting
confidence: 89%
See 4 more Smart Citations
“…In Dutta et al (2016) successful maturation rate was reached 79.9% in A grade group, which is very similar to our control group (74.03%). With porcine A grade oocytes (high quality oocytes after LB staining), the successful maturation rate reached 84.70%, which is almost identical to our LB-oocytes (82.24%).…”
Section: Proteomic Evaluation Of Lb-and Lb+ Oocytessupporting
confidence: 89%
“…Their study also observed a higher competence of C grade group (lower quality after LB staining) to reach MII (62.26%), which is significantly different as our result in LB+ group (22.80%). In Dutta et al (2016), very similar differences were observed after parthenogenetic activation too. Based on the results, we can say that the detection of membrane damage leads to a significant reduction in oocyte developmental potential, which is more important than the detection of damaged cumulus cells.…”
Section: Proteomic Evaluation Of Lb-and Lb+ Oocytessupporting
confidence: 65%
See 3 more Smart Citations